THE EFFECTS OF ENTREPRENEURSHIP EDUCATION, SELF-EFFICACY AND ORIENTATION TOWARD ENTREPRENEURSHIP INTENTION AND ITS’ IMPLICATION ON ENTREPRENEURSHIP COMPETENCE - Hermawan, Yoni, Disman; Ahman, Eeng, Suwatno; Sundari, Ristina Siti (CENTRAL ASIA AND THE CAUCASUS, 2022)
To be an entrepreneur is now the solution to end poverty lead to prosperity. The research aimed to know entrepreneurship education, efficacy, orientation toward entrepreneurship intension, and its' implication on entrepreneurship competence. This research used an explanatory survey method. The research locations were the student of University of Siliwangi, University of Galuh, University of Kuningan, and University of Garut. The sampling took Proportionate Randomized Sampling that had been chosen four Universities regarding 378 respondents. The result showed that entrepreneurship education and efficacy influenced student entrepreneurship intension in West Java that had ever been taken entrepreneurship education. Entrepreneurship orientation also influenced entrepreneurship intension, entrepreneurship education, efficacy, orientation and intension influenced entrepreneurship competence.